Comparison of Risks, Returns and Performance Measurements of Sharia and Non-Sharia Mutual Funds in Indonesia - Yoyok Prasetyo; Mohamad Anton Athoillah; Deni Kamaludin Yusup (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2019)
Investment is a sacrifice to postpone current consumption by allocating a number of assets that are expected to earn benefits in the future. Islamic Sharia does not forbid Muslims to do it, even there is an indication that it is recommended. The main motivation is to be able to pay more alms in the future. One of investment instruments in Indonesia is Mutual Funds. Indonesia's predominantly Muslim population is one of the triggers for the development of sharia-based mutual funds. However, its development has not been as big as the existing potential market. One of the reasons is there is still a view in the community that sharia-based instruments provide lower returns than non-sharia. This study compares the risks and returns of mutual funds, between sharia and non-sharia based. Sampling of both used purposive sampling, where there were 6 sharia mutual funds and 8 non-sharia mutual funds. The study was conducted in 5 years. The results of the study were: (1) There was no significant difference between the risks of both; (2) There was no significant difference between the returns of both; (3) The performance of non-sharia mutual funds was more dominating than sharia mutual funds.